A Trusted System Framework for Electronic Records Management Based on Blockchain - Xue, Sixin; Zhao, Xu; Li, Xin; Zhang, Guigang; Xing, Chunxiao (Web Information Systems and Applications, 2019)
The credibility and authenticity of electronic records determine whether electronic documents have legal effect, preservation value, use effectiveness and reproduction history. Firstly, the existing research was analyzed and the consensus reached is that the reliable technical system is the key to ensure the dual requirements of evidence retention and information utilization during the activities of electronic records management. Secondly, based on the life cycle theory of electronic records and the methodology of whole process continuous management, an application framework of electronic records trusted management based on critical business process management is constructed. And then, according to the technical characteristics and application principle of block chain, the evidence chain model of trustworthy managing electronic records is proposed and the construction of evidence chain model based on type or time limitation with the help of electronic records classification management is studied. Finally, the related key technologies and their application scenarios are analyzed.